ANALYSIS OF THE EFFECT OF ELECTRONIC CUSTOMER RELATIONSHIP MANAGEMENT (E-CRM) AND BRAND TRUST ON CUSTOMER SATISFACTION AND LOYALTY IN PIXY COSMETIC PRODUCTS - Nandya, Tasya; Permana, Dudi (Dinasti International Journal of Management Science, 2021)
The purpose of this study was to study the Analysis of the Effects Electronic Customer Relationship Management (E-CRM) and Brand Trust to Customer Satisfaction and Loyalty to Pixy Cosmetic Brand. by measuring indicators that influence the variables of E-CRM, Brand Trust, Customer Satisfaction and Loyalty. This research uses descriptive research design using survey methods. Sampling uses certain criteria where respondents have known Pixy Cosmetics products from Key Opinion Leader and have bought Pixy Cosmetic Products via E-commerce and Offline store as well, at least 1 time in as a sampling technique. This study discusses using the structural equation model (structural equation modeling) - Lisrel to discuss the significance of the overall model relationship and predetermined pathways. The findings show that the E-CRM variable is positive and significant towards Customer Satisfaction, the Brand Trust is positive and significant towards Customer Satisfaction, and Customer Satisfaction is positive and significant towards the Loyalty.